Citra Perempuan Dalam Novel Geni Jora Karya Abidah El Khalieqy Dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia Di SMA: Tinjauan Feminisme Sastra - HARTOMO, HARTOMO, Prof. Dr. H. Ali Imron Al-Ma'ruf, M.Hum (2016)
This study aimed to describe (1) socio-historical background Abidah El Khalieqy, (2) a novel stucture Geni Jora, (3) forms the image of women in the novel Geni Jora, and (4) implementation as teaching materials Indonesian high school. The method used is qualitative descriptive. The object of this study is the image of women in the novel Geni Jora by Abidah El Khalieqy. Source of data used in the form of primary and secondary data sources, data collection techniques, namely literature, see, and record. Data analysis technique used is the reading of the heuristic method, followed by reading hermeneutics. Based on the analysis performed, it can be summed up as follows: (1) socio-historical background Abidah El Khalieqy, a writer productive has delivered many different types of xii works of literature, especially the genre of feminist literary Islam, it is not free from the influence of the background who live in the neighborhood islamic boarding school, (2) structure in the novel Geni Jora is theme, grooves, character, and setting, (3) image of women were found to be the image of women in the sphere of education, image of women in the sphere of culture, image of women in the sphere of religion, (4) implementation of the research results is relevance of the intrinsic elements and the value of the image of women with KD 3.1 and 4.1 on learning Indonesian class XII, relevance of the formation of personality in participants students, and application of educational values in learning.